Acetic Acid Production from Aspergillus terreus Isolated from Some Agricultural Soils Collected from Selected Locations within the North Gondar Zone, Amhara Region, Ethiopia - Kidist Alemayehu; Tamene Milkessa Jiru; Nega Berhane (International Journal of Microbiology)
Acetic acid, a substance with numerous uses as a bulk chemical, may be produced novelty by Aspergillus terreus. With the newfound understanding of Aspergillus species catabolism of glucose, fermentation techniques for the generation of secondary metabolites like acetic acid in the Ethiopian north Gondar zone can be developed with glucose feeding and pH feedback management. Previous works done on extracting organic acids including acetic acid from filamentous fungi in Ethiopia and at the global level are scanty. Therefore, this study aimed to produce acetic acid from A. terreus isolated from agricultural soils in the north Gondar zone of Ethiopia using barely straw as a substrate. In the current study, Aspergillus isolates were obtained in the samples taken from three different locations. The isolates were screened for acetic acid production. The optimum temperature and pH for the maximum production of acetic acid by the selected isolate were also undertaken. The potential isolates were further cultured using barley straw as a local substrate. Preliminary identification of the selected isolates was based on morphological methods. Molecular characterization (amplification and sequencing of the two intergenic spacers, ITS1 and ITS2, and the intervening 5.8S gene of the ribosomal RNA) was carried out to confirm the identity of the Aspergillus isolates. When the isolates were screened for the production of acetic acid, an isolate from low land (isolate LL2) had the highest yield (72.5 ± 1.65 g/l) on basal screening media. The optimum temperature and pH for the maximum production of acetic acid by this isolate were 30°C and pH 5.0. A sequence similarity of 98.5% to A. terreus isolate LL2 (KIA) was obtained by comparing the Aspergillus isolate to a reference sequence in the GenBank using the BLAST algorithm. It can be concluded from this study that A. terreus isolated from agricultural soil in the north Gondar zone of Ethiopia could produce more acetic acid using barely straw as a substrate.